Exploring the influence of nurses’ demographics and hospital work environment on medical error reporting practices in Jordan: a cross-sectional study - Anas Husam Khalifeh; Ala’a Dalky; Islam Ali Oweidat; Sajeda Ramadan Abuzaid; Mohammed AlBashtawy (BMJ Open)
Objective Nurses have a significant role in maintaining patient and healthcare safety. Thus, healthcare administrators should focus on nurse performance and create a friendly hospital work environment to ensure patient safety and healthcare quality. Limited studies have investigated the impact of nurses’ demographics on nurses’ error reporting practices and nurses’ perceptions of the hospital work environment, especially in Jordan. This study aims to investigate the factors influencing nurses’ medical error reporting practices in Jordan, specifically focusing on the role of nurses’ demographics and the hospital work environment.Design: This is a descriptive cross-sectional study.Setting Data collection was done in three hospitals (public, university-affiliated and private) in Jordan, using surveys that included demographics, the incident reporting practice scale and the Practice Environment Scale-Nursing Work Index from 11 June 2023 to 13 August 2023.Participants 350 nurses with a diploma, associate degree, bachelor’s degree or postgraduate degree had worked at the targeted hospitals for at least 6 months and were responsible for direct inpatient care.Primary outcome measure The level of medical error reporting practices and the nursing work environment. Also, differences were assessed among demographic characteristics and investigated the factors for medical error reporting practices.Results Jordanian nurses had low medical error reporting practices (M=2.34; SD=0.57) and nursing work environment (M=2.4; SD=0.56). Nurses who were single and in private hospitals had higher medical error reporting practices (p<0.05). Medical error reporting practices positively correlated with the nursing work environment (r=0.807, p<0.01) and negatively correlated with the average number of patients per shift (r=−0.109, p<0.05). The nursing work environment was a significant predictor, with an 81.0% variance in medical error reporting practices.Conclusions The study found that Jordanian nurses have low perceptions of their work environment and medical error reporting practices, which are influenced by marital status and hospital type. Enhancing the nurse work environment and providing ongoing standards training are critical for improving safety behaviours, patient outcomes and care quality. Future research should investigate the long-term consequences of interventions on reporting practices and patient outcomes.